RANCANG BANGUN SISTEM INFORMASI GEOGRAFIS PENGEPUL KOPI BERBASIS ANDROID - Kendrawan, I Dewa Gede Shunu; Khrisne, Duman Care; Sukadarmika, Gede (SINTECH (Science and Information Technology) Journal, 2018)
The low income of coffe farmers in Indonesia is  caused several factor, large production cost, non standart prices and high transport costs. In this paper we try to overcome this problem by establishing a geographic information system for coffe collectors, that will help farmers find an appropriate buyer with minimal shipping costs to maximized their profits. This research has been successfully implemented using Google Maps API for mapping the location and built as an Android based mobile devices application. Application on the side of the collectors can input different types of coffe prices to be purchased. While the system is on the side of farmers can search for  coffe collectors location. The test results using the system usability scale (SUS), the respondents gave a score on the farmer’s average of 74.7 and the side of the collector of 71.1 which means it has value adjective rating = excellent, grade scale = c and acceptability ranges = acceptable.